DIGITAL-BASED LANGUAGE TESTING IMPLEMENTATION DESIGNED FOR EFL LEARNERS - Magdalena Kartika Sari Tandy Rerung; Junita Hartono (Acitya: Journal of Teaching and Education, 2020)
The technology-based test has been a controversial issue during the last decade. On the other hand, it can offer solutions for an effective long-distance learning or e-Learning program which can be applicable in the situations where learning process is limited either in physically or time-constraint. Despite of monitoring students’ progress assessment is needed to evaluate whether the learning process is effective or not. With the intervention of internet and technology in the education field, this offers many ways to apply assessment for the learning progress. Web-based-test (WBT) offers a great varieties and features which is easily accessed. Furthermore, this research used two kinds of WBT, namely Google Form and Quizizz to look further of some benefits from these types of tests also to investigate its effectiveness. The following study applied the quantitative method where scoring result is gathered and calculated to measure the average score and the most preferable test-method. There were around 66 university students from two different majors. They were taking Business English at their second semester in Bunda Mulia Universit. The tests were conducted during the online program due to the pandemic situation. The finding reveals that both tests have its strongest and weakest points whereas the better result shows that Quizizz is higher than in Google Form.